2022
DOI: 10.1002/ccr3.6338
|View full text |Cite
|
Sign up to set email alerts
|

Classical Ehlers–Danlos syndrome with severe kyphoscoliosis due to a novel pathogenic variant of COL5A2

Abstract: Ehlers-Danlos syndromes (EDS) are a heterogeneous group of hereditary connective tissue disorders (HTCD) caused by mutations in genes involved in the structure and/or biosynthesis of collagens and other extracellular matrix proteins. 1 The 2017 classification consists of 13 types of EDS based on clinical manifestations and genetic abnormalities in 19 different genes. 2 Main common characteristics are generalized joint hypermobility (GJH), skin hyperextensibility, and tissue fragility. Scoliosis is another comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the other hand, the effectiveness of bracing therapy in syndromic scoliosis may be limited because the deformity occurs earlier in life and is often more progressive than in idiopathic scoliosis. One study showed that bracing was most effective in children with a spinal curvature above 20°–25° who were too old for casting in a cohort of scoliosis patients with Prader–Willi syndrome [ 23 ]. Bracing is intended to stop curve advancement.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the effectiveness of bracing therapy in syndromic scoliosis may be limited because the deformity occurs earlier in life and is often more progressive than in idiopathic scoliosis. One study showed that bracing was most effective in children with a spinal curvature above 20°–25° who were too old for casting in a cohort of scoliosis patients with Prader–Willi syndrome [ 23 ]. Bracing is intended to stop curve advancement.…”
Section: Introductionmentioning
confidence: 99%
“…Bracing is intended to stop curve advancement. However, in cases of very large curves, braces may be used to maintain the curve until the patient is ready for surgery [ 23 ]. Generally, 5 of less than 30° are treated with a Providence-style brace that is only worn at night [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations